MUSEUM TEMBIKAR DAN KERAJINAN TANGAN DENGAN PENDEKATAN BANGUNAN PINTAR DI MAKASSAR - Basran, Muhammad Akbar; Burhanuddin, Burhanuddin (Nature: National Academic Journal of Architecture, 2015)
City centrum South Sulawesi, Makassar as containing many historical values in it would strongly support the existence of the museum. Makassar is potentially the city both in terms of location or condition of the orientation of the Municipality of Makassar easily accessible from other areas in South Sulawesi itself, or from areas outside South Sulawesi because of the availability of means of transportation by land, sea and air are very supportive. Planning museum pottery with application of smart buildings is expected to be a breakthrough in dealing with problems in buildings, especially commercial buildings and in addition to the procurement of museum pottery in the city is expected to be a means indulge the public by presenting the shape and feel of the building attractive to become the fascination of the consumers and students in the building pottery museum in the city of Makassar. As one attempt to do that with the provision of a special representative container that can guarantee the effort to preserve objects of handicraft city of Makassar.